2015
DOI: 10.1007/s10545-015-9881-1
|View full text |Cite
|
Sign up to set email alerts
|

Child and family experiences with inborn errors of metabolism: a qualitative interview study with representatives of patient groups

Abstract: BackgroundPatient-centered health care for children with inborn errors of metabolism (IEM) and their families is important and requires an understanding of patient experiences, needs, and priorities. IEM-specific patient groups have emerged as important voices within these rare disease communities and are uniquely positioned to contribute to this understanding. We conducted qualitative interviews with IEM patient group representatives to increase understanding of patient and family experiences, needs, and prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 33 publications
10
73
1
1
Order By: Relevance
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 79%
“…Families’ concerns about the social development of children with IMD may be exacerbated during life transitions, particularly adolescence [25, 27], and may be more prevalent for IMD characterized by significant physical disability [25]. In our study we identified social challenges in families of relatively young children (up to age 7) that were mainly connected to the need for specialized diets, and thus we were unable to corroborate previous research about transitions to adolescence and adulthood.…”
Section: Discussioncontrasting
confidence: 62%
“…Importantly, adolescents reported less frequently about social support than younger patients but still encountered experiences of stigmatisation, resulting in an imbalance of constraints and resources. Our results thereby suggest that transitional phases (to school, to adolescence), often combined with social and physical challenges, deserve special attention, as this has been reported before for other inborn errors of metabolism (Packman et al 2012;Khangura et al 2015). Sharing meals with others is known to have high social significance; hence, patients living with dietary restrictions experience numerous potentially stigmatising situations (Diesen et al 2014).…”
Section: Discussionsupporting
confidence: 63%
“…Our results suggest that families with young children in particular would benefit from support targeting these uncertainties and coping with diagnosis and treatment. In addition, immediately at diagnosis, patients should be informed about support groups, which have been shown to be important informational resources in rare disorders (Hall 2013;Khangura et al 2015). Accordingly, the majority of participants in this study greatly appreciated the exchange with others in the context of the interviews and expressed their wish to have this opportunity more frequently.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the use of HrQoL instruments generally improves communication between patients and the medical team, which results in enhanced patients' wellbeing (Velikova et al 2004). This is of particular importance during transitional phases such as transition to kindergarten, to school, and to adolescence (Packman et al 2012;Khangura et al 2015), when the impact of the disease and specific needs may change.…”
Section: Discussionmentioning
confidence: 99%